SEJARAH BALAGAH: ANTARA MA’RIFAH DAN SINĀ’AH - Ibnu Samsul Huda (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
When the literary world enters the realm of scientific study, the arbitrariness and the infinity of expression, which is the main characteristic of literary work, should be evaluated based on an objective standard of science. Balagah, a literary theory born and developed in Arab, has also undergone a process of standardization of concepts and theories as other sciences. This paper describes the history of balagah from embryonic phase until it has been structured to be a science with a set of scientific theories. A historical approach is expected to be able to reveal historical facts related to the codification of balagah since the beginning of its existence until its latest development. The systematization and theorization of balagah had been done since there was a trend of translations of Greek philosophy into Arabic. The demand of scientific knowledge in Greek tradition greatly endorsed the theorizing of balagah. Standardization of the theory of balagah positively facilitates learners to understand the science of balagah and to have scientific accountability. However, the systematization of balagah has led this study to a static condition. In addition, the orientation of balagah is more in linguistic (syntax) area.Simak